Economic feasibility of glasshouse tomato production in China — A bio-economic stochastic modelling approach. Issue 1 (31st December 2022) - Min, Xinyuan; Sok, Jaap; Elings, Anne; Oude Lansink, Alfons
ABSTRACT: Glasshouse investments are booming in China, even little is known about the economic feasibilities and uncertainties of such investments. This study employed a bio-economic model to assess the economic feasibility and uncertainties of an investment in a Venlo-type glasshouse for cherry tomato production in four regions in China: Jinshan, Langfang, Weifang, and Pingliang, with different climate and market conditions. A bio-physical model for tomato yield and energy use simulation was calibrated with the climate and production data from 2019 to 2020 of a commercial glasshouse in Shanghai, China. The average yield and energy use for each region were simulated with the temperature set points provided by a grower and 30-year climate data. The distributions of the Net Present Values (NPVs) were determined using Monte Carlo simulation which addressed uncertainty due to stochastic seasonal tomato and natural gas prices. The economic outcome of tomato glasshouse investment varies across regions, with a mean NPV ranging from −957.8 ¥ m −2 for Weifang, to 477.0 ¥ m −2 for Pingliang. A sensitivity analysis suggests that variations in natural gas prices have larger impacts on the net cash flow than tomato prices. This study contributes to the research on glasshouse modelling by introducing seasonality and uncertainties of prices in a bio-economic model of a glasshouse farm. The results of this study can inform investors of the economic outcomes and the risks of glasshouse investments. They can also aid Chinese local governments to design agricultural support policies that suit the regional climate and market conditions. Graphical abstract: uf0001